TEST-SYSTEM FOR ESTIMATION OF ACTIVITY OF GSK-3 INHIBITORS AS ANTIHYPOXANTS AND DIFFERENTIATION OF ENDOTHELIAL PROGENITORS IN VITRO - Youri Burda; Sergey V. Nadezhdin; Ekaterina Zubareva; Mikhail Pokrovskii; Alexander Faitelson; Svetlana Burda; Maria Shirina (Belgorod National Research University, 2016)
A model test-system was developed for validation in vitro of antihypoxic and endothelio-differentiating activity of newly created glycogen synthase kinase-3 inhibitors in comparison with the reference drug β4-thymosin.